WEWENANG PERHIMPUNAN ADVOKAT INDONESIA DALAM PENGUSULAN PENYUMPAHAN ADVOKAT (Analisa Yuridis Atas Putusan Mahkamah Konstitusi Nomor 35/PUU-XVII/2018) - Syahrul Sitorus (Hikmah, 2019)
PERADI is an abbreviation of the Indonesian Advocates Association, it exists as an advocate organization which is a forum for the advocate profession. Establishment of PERADI, PERADI's professional development and oversight authority is fully exercised by PERADI. The authorities include: Carrying out special education of the Advocate profession; Testing for Advocate candidates; Appointment of Advocates; Make a code of ethics; Establish an Honorary Board; Establish a Supervisory Commission; Supervise; and Dismiss Advocates.